PEMETAAN RISIKO BENCANA BANJIR SUNGAI BOGOWONTO HILIR - , Hudzaifah All A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Flood is a disaster that could threaten and disturb human life and activity, might be caused by nature or human activity, resulting in life casualties, environmental damage, property loss, and psychological impact. The Bogowonto River floods almost every year in rainy season and mostly affects in downstream area. Downstream of Bogowonto River has 38,69 km long, slope < 0,5%, elevation between 0 to 50 m, and 231,15 kmÂ² catchment area. Objective of this research is to develop flood risk map for 3 (three) sub-districts (kecamatan) in downstream area of Bogowonto River: Kecamatan Ngombol, Kecamatan Purwodadi, and Kecamatan Bagelen. Hydrologic and hydraulic modeling combined with hazard, vulnerability, and capacity analysis ware used to determine flood risk and mapping. Flood event on January 2, 2012 with maximum discharge at 1030.19 m3/s was used for model simulation. Vulnerability and capacity analysis using parameters from PerKa BNPB No.2 Tahun 2012, and risk analysis methods were based on Perka BNPB No.4 Tahun 2008. HEC-RAS, Arc-GIS and Word Processor were used for analyzing data. Hydraulic analysis of Bogowonto River using prescribed data result in overflow at several locations. Overflow volume is 3.576.570 m3 and affected area is 125,6 Ha in Kecamatan Purwodadi and 86.2 Ha in Kecamatan Bagelen. Based on risk map result, villages that prone to flooding are: Soko, Kalirejo, Bapangsari, Dadi Rejo, Karang Mulyo, Ketangi, Bubutan, Sido Harjo, Kebonsari, Banjarsari and Karangsari.